HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELINCAHAN DENGAN KEMAMPUAN MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA PADA UNIT KEGIATAN MAHASISWA PENJASKES STKIP SETIA BUDHI RANGKASBITUNG - Sudirman, Ridwan (STKIP Setiabudhi, 2018)
The aim of the study was to find out whether there was a relationship between leg muscle explosive power and agility on the ability to dribble the ball in the student soccer game of the student unit of STKIP Setia Budhi Rangkasbitung student activity. The method used in this research is descriptive method used to try to solve problems or answer the problems faced, which are carried out by taking steps, collecting classifications and analyzing data collection, making the depiction of a situation objectively in a descriptive situation. Descriptive are: 1) the relationship between leg muscle explosive power and the ability to dribble, 2) the relationship between agility to the ability to dribble, 3) the relationship between the two variables on the ability to dribble the ball of students of the STKIP Setia Budhi Rangkasbitung student activity unit. Based on the results of the analysis and calculation of data, it can be concluded that: 1) There is a significant relationship between the explosive power of leg muscles and the ability to dribble. 2) There is a significant relationship between agility and ability to dribble. 3) There is a significant relationship between leg muscle explosive power and agility on the ability to dribble the ball in the student soccer game of the student unit of STKIP Setia Budhi Rangkasbitung student activity.